Administration of intercollegiate athletics - Weight, Erianne A. PhD, MBA 1981-; Zullo, Robert H. PhD 1975- (Champaign, IL Human Kinetics, 2025)
The text provides you with an overview of the daily operations and inner workings of intercollegiate athletics departments. The foundational knowledge is paired with chapter-by-chapter leadership lessons, discussion questions, and learning activities, including case studies. This updated edition includes industry profiles, technology tools, and professional development resources. It also adds a new chapter devoted completely to diversity, equity and inclusion. The text focuses on larger NCAA-governed institutions but also includes examples of policies and procedures for governance and management structures that vary depending on the resources and objectives of a school, including those at Division II, Division III and other levels
Chapter 1 A brief historical perspective on intercollegiate athletics -- Chapter 2 Governing bodies -- Chapter 3 Leadership and management -- Chapter 4 Compliance -- Chapter 5 Diversity, equity, and inclusion -- Chapter 6 Academics, eligibility, and student-athlete development -- Chapter 7 Media relations -- Chapter 8 Financial operations -- Chapter 9 Marketing -- Chapter 10 Corporate sponsorship -- Chapter 11 Facility and event management -- Chapter 12 Alumni relations and athletics development -- Chapter 13 Support services
First edition: 2015
Includes bibliographical references and index
Keywords: National Association of Intercollegiate Athletics; National Collegiate Athletic Association; College sports -- United States -- Management